If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3X + (-6) = -12 3X + -6 = -12 Reorder the terms: -6 + 3X = -12 Solving -6 + 3X = -12 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3X = -12 + 6 Combine like terms: -6 + 6 = 0 0 + 3X = -12 + 6 3X = -12 + 6 Combine like terms: -12 + 6 = -6 3X = -6 Divide each side by '3'. X = -2 Simplifying X = -2
| 3x^2-y^2+12x+4y-2=0 | | 1/3(45x-18/7) | | 4(y+8)=9y+27 | | 5(2)8t=15 | | 3w-18=6(w-2) | | 15/8=5y | | zy^4/z^7y^3 | | -5=a+4 | | C=-12X+15 | | u^2-2u-3= | | -5v+3(v+5)=21 | | u^2+8u+7= | | a^2x+(a-9)=(a+9)x | | 2(x-4)-5x=-32 | | 9/15-3/25 | | -8w+5(w+2)=-17 | | 5.25/7 | | 15x*4-8x+3+3x*4-2x+1= | | x^2-9x-67=0 | | -91=6y-15y-19 | | -8w+5(w-3)=-6 | | 2x+41+3x=6 | | -20=4v+8(v+2) | | -6w-7w-27=28 | | x^2-28x-288=0 | | -8=4(y+2)-8y | | 14=2u+6(u-3) | | 6(w+4)-4w=18 | | 2x^6+15x^3-8=0 | | X^3/x^2-9 | | 4ln((x/4)^2-1) | | -7(x-9)+7=70 |